An enhanced X-ray imaging contrast using a grating-based talbot interferometry - Liew, Seaw Jia (2016)
We often deal with objects made of low-density materials in various settings, such as soft biological tissues in the medical sciences and manufacturing of food, and low-density polymeric substances in the manufacturing of medical devices and automotive parts. Inspection of low-density materials using the conventional X-ray imaging that is based on the principle of X-ray absorptions often results in a lack of image contrast because these materials do not generate satisfactory absorptioncontrast under the irradiation of typical range of hard X-rays. Furthermore, in many cases, the objects always come in irregular form of shapes and sizes, this makes the X-ray imaging challenging as different X-ray energies are required to penetrate through different range of object thickness in order to provide a satisfactory visibility of fine defects and structural profiles residing beneath the surface.